Annonaceae: Breaking the Wall of Inflammation - Attiq, Ali; Jalil, Juriyati; Husain, Khairana (Frontiers in Pharmacology, 2017)
Inventories of tropical forests have listed Annonaceae as one of the most diverse plant families. For centuries, it is employed in traditional medicines to cure various pathological conditions including snakebite, analgesic, astringent, diarrhea, dysentery, arthritis pain, rheumatism, neuralgia and weight loss etc. Phytochemical analysis of Annonaceae family have reported the occurrence of alkaloids, flavonoids, triterpenes, diterpenes and diterpene flavone glycosides, sterols, lignans and annonaceous acetogenin characteristically affiliated with Annonaceae sp. Numerous past studies have underlined the pleotropic pharmacological activities of the crude extracts and isolated compounds from Annonaceae species. This review is an effort to abridge the ethnobotany, morphology, phytochemistry, toxicity and particularly focusing on the anti-inflammatory activity of the Annonaceae species.